SLIPS OF THE TONGUE IN INDONESIAN DAILY CONVERSATION: A PSYCHOLINGUISTIC VIEW - Merry Lapasau; Sulis Setiawati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: This research aims at analyzing speech errors, also known as slips of the tongue madeby adult Indonesians as native speakers. Those errors were analyzed regarding types andbackground of the occurence with Meringer’s theory of slips of the tongue as the framework ofthe research. This research is mainly qualitative with a descriptive approach within thepsycholinguistics view. The results show that slips of the tongue occurred by adult Indonesian asnative speakers were: 1. Exchange, 2. Anticipation, 3. Postposition, 4. Contamination, and 5.Substitution. Researchs about slips of the tongue can provide input to the language process whichis very important for language teaching. Language teachers can interact better with students if theproblems as the sources of the students' errors are identified. Above all, by comprehending varioustypes of speech errors we can increase our understanding of the acquisition, production, andperception of our language thoroughly.Key Words: speech error; slips of the tongue; psycholinguistics